Methods for protein delivery into cells: from current approaches to future perspectives. (8th April 2020) - Chau, Chalmers; Actis, Paolo; Hewitt, Eric
Abstract : The manipulation of cultured mammalian cells by the delivery of exogenous macromolecules is one of the cornerstones of experimental cell biology. Although the transfection of cells with DNA expressions constructs that encode proteins is routine and simple to perform, the direct delivery of proteins into cells has many advantages. For example, proteins can be chemically modified, assembled into defined complexes and subject to biophysical analyses prior to their delivery into cells. Here, we review new approaches to the injection and electroporation of proteins into cultured cells. In particular, we focus on how recent developments in nanoscale injection probes and localized electroporation devices enable proteins to be delivered whilst minimizing cellular damage. Moreover, we discuss how nanopore sensing may ultimately enable the quantification of protein delivery at single-molecule resolution.